Peers Keep It Real: Re-engaging Adults in HIV Care. (4th April 2019) - Enriquez, Maithe; Cheng, An-Lin; McKinsey, David; Farnan, Rose; Ortego, Gerry; Hayes, Deana; Miles, LaTrischa; Reese, Michael; Downes, Alicia; Enriquez, Amanda; Akright, Jan; El Atrouni, Wissam
Background: After diagnosis, a substantial number of people with HIV disease fall out of care. Effective interventions are needed for this priority population. Methods: The "Peers Keep It Real" study aimed to help adults who were disengaged from HIV treatment. Peers, lay individuals living with HIV, facilitated intervention sessions. Participants were randomized to immediately receive the peer-facilitated intervention or were wait-listed. Results: Considerable attrition occurred in the control group. Pre-/postanalyses showed that among participants (n = 23) who received the intervention, 65% had viral load suppression and 100% remained in care at 12 months postintervention. Impact on viral load was significant ( P = .0326), suggesting that peers are effective change agents who positively impacted outcomes for individuals struggling with adherence to HIV treatment. Conclusion: Future endeavors should consider providing all individuals from this priority population with an active peer intervention from the onset to enhance retention and adherence.